Organizing the Formation of the Presidential Cabinet in Indonesia: A Comparative Analysis with the United States, the Philippines, Argentina, and South Africa - M. Yasin al Arif; Elif Yaren Çalkacı (CV. FOUNDAE, 2025)
The formation of a cabinet is a central element in the presidential system for creating impactful governance that directly affects the effectiveness and efficiency of public policies. This study focuses on comparing the mechanisms and dynamics of cabinet formation in the United States, the Philippines, Argentina, and South Africa, as well as analysing its potential application in the Indonesian context. The research questions posed are: how are cabinets formed in the United States, the Philippines, Argentina, and South Africa, and how does this comparative analysis relate to the future structuring of the Indonesian cabinet? This study adopts a normative juridical research methodology. The approaches used include the statute approach, comparative approach, and conceptual approach, utilising secondary data comprising primary, secondary, and tertiary legal materials. The research findings conclude that various cabinet formation models in the United States, the Philippines, Argentina, and South Africa show significant variations in appointment mechanisms, accountability, transparency, and meritocracy. Despite differences in legal and political contexts, fundamental principles such as accountability and transparency are essentially the cornerstones of the cabinet formation systems of these nations. Through this study, suggestions for the future improvement of the Indonesian cabinet formation are proposed, such as the adoption of the American